Ekotoxikologické hodnocení vybraných průmyslových odpadních materiálů a anorganických kompozitů s jejich obsahem - Pavlitová Letková, Zuzana (Vysoké učení technické v Brně. Fakulta chemická, 2011)
Tato disertacní práce shrnuje výsledky testu ekotoxicity, které byly provádeny na ruzných druzích prumyslového odpadního materiálu jako jsou klasické popílky, fluidní popely a popílky, škváry, strusky a také na anorganických kompozitech s obsahem tohoto odpadu, které by mohly být v budoucnu použity jako stavební hmoty. Pro posouzení ekotoxicity byly využity testy akutní toxicity na testovacích organismech: akvarijní rybe (Poecilia reticulata), perloocce (Daphnia magna), sladkovodní rase (Raphidocellis subcapitata). Ekotoxicita byla hodnocena i testem inhibice rustu korene horcice bílé (Sinapis alba). (Vyhodnoceno dle Vyhlášky c. 294/2005 Sb.) Z kontaktních testu byly vybrány testy s roupicemi, chvostokoky a salátem. Bylo realizováno prímé srovnání testu klasického se semeny horcice a kontaktního testu se semeny salátu. Výsledkem pro testy ekotoxicity bylo urcení procentuální mortality, imobilizace, stimulace nebo inhibice rustu pro testované organismy. Bylo provedeno srovnání výsledku jednotlivých testu ekotoxicity a porovnání klasicky provedených akvatických testu a testu kontaktních realizovaných v umelé pude.

This work sums up results of tests of ecotoxicity that were made on different kind of industrial waste materials like classical ash, fluid and fly ash, slags as well as anorganic composites containing waste materials. Composites might be used for building materials in the future. Ecotoxicological tests were used for evaluation of ecotoxicity, represented by 4 trophic levels, with several bioindicators evaluated at different exposure time periods. The battery of classical tests includes a growth inhibition test of the freshwater alga Raphidocellis subcapitata, an immobilization test of the cladoceran Daphnia magna and freshwater fish Poecilia reticulata and a test of inhibitive effects on the root growth of white mustards Sinapis alba. Tests with enchytraeidae, collembolan and lettuce were chosen from group of contact tests. It was realized confrontation between classical test with seeds of mustard and contact tests with seeds of lettuce. Results of ecotoxicity tests were determination of percentage of mortality, immobilization, stimulation or inhibition of growth for testing organisms. It was made comparison of results individual ecotixicity tests. Results of classical aquatic tests were compared with contact tests realized in artificial ground.
Ecotoxicological Evaluation of Industrial Waste Materials and Anorganic Composites Containing Waste Materials
Keywords: Ekotoxikologické testy; kontakní biotesty; odpady; kompozity s obsahem odpadu; Ecotoxicological tests; contact biotets; waste materials; composits with waste